Theoretical And Methodological Approaches Of State And Civil Society Relations (Eurasian Journal of Humanities and Social Sciences, 2025)
The article argues that the current realities of modern societies indicate the need for a deep study of the scientific foundations of civil society and its comprehensive analysis. At the moment, civil society can be assessed as the current level of information and communication capabilities, various migration flows, and the level of renewal of ethnic groups. In addition, the development of civil society, which is a specific expression of the needs of citizens and reflects them in the political system, is of great importance. In this sense, it is stated that civil society is one of the most important conditions for building a legal state.